Reconstructing Zakat Governance Through Qur’anic Perspectives - Dian May Syifa; Budi Rahmat Hakim; Yulia Hafizah; M Yakhsyallah Liddinillah; Rena Zulfaidah; Farid Hamdani (Universitas Negeri Padang, 2026)
Zakat management in Indonesia faces a critical challenge regarding the legal ambiguity between private and public domains, leading to low accountability and latent corruption risks within zakat institutions. This study aims to reformulate the conceptual foundations of zakat governance by integrating Al-Quran's normative values into a modern governance framework. Employing a qualitative method with a thematic interpretation (maudhu’i) approach, this research analyzes Quranic verses concerning institutional legitimacy (QS. At-Taubah: 103), distribution principles (QS. At-Taubah: 60), wealth ethics and anti-manipulation (QS. Al-Baqarah: 264, 267) and verses on integration of social worship (QS. Al-Baqarah: 110). The findings reveal that the Al-Quran mandates an integration between ritual piety and social justice, where the state holds a constitutional role as a facilitator through the principle of